#### Answer

$-\dfrac{5}{2}*x$

#### Work Step by Step

$-\dfrac{1}{2}*(5*x)=(-\dfrac{1*5}{2})*x=-\dfrac{5}{2}*x$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$-\dfrac{5}{2}*x$

$-\dfrac{1}{2}*(5*x)=(-\dfrac{1*5}{2})*x=-\dfrac{5}{2}*x$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.